BMP signaling during craniofacial development: new insights into pathological mechanisms leading to craniofacial anomalies - Ueharu, Hiroki; Mishina, Yuji (Frontiers in Physiology, 2023)
Cranial neural crest cells (NCCs) are the origin of the anterior part of the face and the head. Cranial NCCs are multipotent cells giving rise to bones, cartilage, adipose-tissues in the face, and neural cells, melanocytes, and others. The behavior of cranial NCCs (proliferation, cell death, migration, differentiation, and cell fate specification) are well regulated by extracellular signaling; abnormalities in their behavior are often reported as causative reasons for craniofacial anomalies (CFAs), which occur in 1 in 100 newborns in the United States. Understanding the pathological mechanisms of CFAs would facilitate strategies for identifying, preventing, and treating CFAs. Bone morphogenetic protein (BMP) signaling is an extracellular signaling playing an important role in a multitude of cellular processes during embryonic development. We and others have reported that abnormalities in BMP signaling in cranial NCCs develop CFAs in mice. Abnormal levels of BMP signaling cause miscorrelation with other signaling pathways such as Wnt signaling and FGF signaling, which mutations in the signaling pathways are known to develop CFAs in mice and humans. Interestingly, few cases are reported showing BMP-related CFAs in humans despite comprehensive studies with transgenic mice showing BMP-related CFAs, suggesting that human embryos with BMP mutations undergo embryonic lethality before developing craniofacial region. In this review, we will summarize the recent advances in the understanding of BMP signaling during craniofacial development in mice and describe how we can translate the knowledge from the transgenic mice to CFAs in humans.